2010
DOI: 10.3109/09593981003761509
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary effectiveness of preoperative therapeutic exercise in patients with cancer: A pragmatic study

Abstract: The aim of this pilot study is to determine the feasibility and preliminary effectiveness of an individually designed preoperative therapeutic exercise program (PreTEP), in patients recently diagnosed with cancer and awaiting elective surgery. The purpose is to improve their physical fitness levels during this waiting period with the intention of decreasing postoperative morbidity. A preexperimental pilot study was performed at the University Medical Center Utrecht, The Netherlands. Thirty-nine patients diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…However, of the patients eligible for the exercise program based on the available time until surgery, 68% participated in the exercise program. A participation rate of 68% is reasonable, since other preoperative training studies report lower participation rates [19,37]. Having to travel to the outpatient hospital clinic twice a week was the most frequently reported reason for non-participation, which is in line with an earlier reported pilot study [19].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, of the patients eligible for the exercise program based on the available time until surgery, 68% participated in the exercise program. A participation rate of 68% is reasonable, since other preoperative training studies report lower participation rates [19,37]. Having to travel to the outpatient hospital clinic twice a week was the most frequently reported reason for non-participation, which is in line with an earlier reported pilot study [19].…”
Section: Discussionsupporting
confidence: 81%
“…Research on prehabilitation programs aimed at improving the overall exercise capacity and muscle strength before surgery is less common. Only a few pilot studies have investigated the effect of an exercise program before oncological surgery [9,19]. For this reason, a preoperative exercise program was designed to improve the physical status of patients scheduled for gastrointestinal oncological surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies were identified and underwent full text review [14][15][16][17][18][19][20][21][22] (Figure 1). One hundred and twenty two studies were identified from the initial literature search and twenty-one from handsearching the study references and through other sources.…”
Section: Description Of Included and Excluded Studiesmentioning
confidence: 99%
“…Nine studies underwent full text review and one of these studies was excluded as it included non-colorectal cancer patients [14]. Therefore, eight studies were included in the qualitative synthesis.…”
Section: Description Of Included and Excluded Studiesmentioning
confidence: 99%
“…There is however a dearth of evidence in this area. One pilot study by Timmerman et al (5), examined the impact of a pre-operative exercise programme only in 39 cancer patients scheduled for elective surgery, included five oesophageal cancer patients, and found significant improvements in exercise capacity could be achieved pre-operatively. Considerable work is required to identify suitable exercise modalities for this purpose.…”
mentioning
confidence: 99%